Agile Mindset as a Microfoundation of Dynamic Capabilities and Organizational Agility in SMEs: A Decade of Evidence - Herdiansyah Gustira Pramudia Suryono; Gatot Yudoko; Yuliani Dwi Lestari (Image : Jurnal Riset Manajemen, 2025)
This study synthesizes a decade of empirical evidence on how Dynamic Capabilities (DC), Organizational Agility (OA), Agile Mindset (AM), and Firm Performance (FP) interact in small and medium enterprises (SMEs). Although dynamic capabilities and organizational agility are widely studied, existing research largely overlooks the cognitive and behavioral conditions that enable these capabilities to function effectively. Using a systematic literature review of 61 peer-reviewed articles (2014–2025) following PRISMA 2020 protocol, with thematic synthesis and VOSviewer bibliometric mapping, this study finds that organizational agility mediates the DC–FP relationship in 55.7% of reviewed studies, but only when an agile mindset is present. Among studies examining agile mindset, 73.7% confirmed its role as a behavioral moderator rather than a standalone variable. This review proposes that sustainable agility in SMEs demands both structural dynamic capabilities and the deliberate cultivation of agile mindset through leadership development and learning-oriented practices.